Strategi Penguatan Layanan Bimbingan Karier Sebagai Upaya Meningkatkan Kesiapan Karier Siswa SMK - Nizar, M. Samsul; Sukoco, Yusab; Komiyati, Komiyati; Kuat, Tri (Indo-MathEdu Intellectuals Journal, 2026)
Career guidance services play an important role in preparing vocational high school (SMK) students to face the demands of a dynamic and competitive world of work. However, its implementation in SMKs still faces various obstacles, including limited systematic programmes, lack of integration with the curriculum, and suboptimal collaboration with the business and industrial world (DUDI). This study aims to examine strategies for strengthening career guidance services in improving the career readiness of SMK students. The method used is a literature study by analysing various research results and scientific publications relevant to career guidance services, career readiness, and vocational education. The results of the study show that career guidance services can be strengthened through comprehensive programme planning, integration of services with the SMK curriculum, utilisation of media and technology, and strengthening collaboration with parents and DUDI. These strategies contribute positively to improving students' career readiness, both in terms of self-understanding, career planning, and readiness to enter the world of work. These findings are expected to serve as a reference for schools and guidance and counselling practitioners in developing effective and sustainable career guidance services.